The End of the "Liberal Theory of History"? Dissecting the U.S. Congress' Discourse on China's Currency Policy - Nicola Nymalm (German Institute of Global and Area Studies (GIGA), 2011)
In the last ten years, economic issues related to currency policy have become the major ongoing dispute between China and the U.S. Especially the U.S. Congress is stridently demanding a tougher policy to avert the negative consequences for the U.S. economy of 'unfair' Chinese policies in the form of a 'manipulated currency.' Building on an analytical framework of discourse theory (DT)-and furthermore proposing a method for applying DT in empirical research- an investigation of the congressional debates on the Chinese currency shows that the question is not a purely economic one, but that it reflects a dislocation of U.S. identity as the vanguard of liberal-democratic capitalism. This implicates changes in regard to how 'liberal' identity in the U.S. is constructed in relation to the role attributed to 'illiberal' China, which in turn affects the formulation of China policy by the U.S. Congress.
Keywords: 300; China; U.S. Congress; economy; currency; identity; liberalism; discourse theory; discourse analysis